Chapter: 'How to Attract Students' Visual Attention' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Danyal Farsani (Lecture Notes in Computer Science, 2016)
Attracting students' visual attention is critical in order for teachers to teach classes, communicate core concepts and emotionally connect with their students. In this paper we analyze two months of video recordings taken from a fourth grade class in a vulnerable school, where, every day, a sample of 3 students wore a mini video camera mounted on eyeglasses. We looked for scenes from the recordings where the teacher appears in the students' visual field, and computed the average duration of each event. We found that the student's gaze on the teacher lasted 44.9 % longer when the teacher gestured than when he did not, with an effect size (Cohen's d) of 0.69. The data also reveals different effects for gender, subject matter, and student Grade Point Average (GPA). The effect of teacher gesturing on students with a low GPA is higher than on students' with a high GPA. These findings may have broad significance for improving teaching practices.